Implementasi Pembelajaran Tahfidz Juz Amma sebagai Upaya Penguatan Kecerdasan Spiritual Siswa - MOH RIZAL RIFAI (Bahasa Indonesia, 2026)
ABSTRACT Education is not merely directed toward the development of students’ cognitive abilities but also toward the cultivation of affective and spiritual dimensions that support their overall character and life competencies. This study aims to examine the role of the Tahfidz Juz Amma learning program in enhancing students’ spiritual intelligence through the implementation of the wahdah, tasmi’, and muraja’ah methods. The research employed a qualitative descriptive approach to gain a comprehensive understanding of the learning process and its impact on students’ spiritual development. Data were collected through observations and in-depth interviews with teachers and students involved in the Tahfidz program. The findings indicate that the implementation of Tahfidz Juz Amma contributes significantly to the improvement of students’ spiritual intelligence. Through the wahdah method, students develop gratitude by recognizing their memorization abilities as blessings from Allah. The tasmi’ method fosters honesty, cooperation, social awareness, and responsibility in their interactions both within and outside the school environment. Meanwhile, the muraja’ah method nurtures patience, consistency (istikamah), and discipline through the continuous practice of memorization and Qur’anic recitation. The study concludes that Tahfidz Juz Amma learning not only strengthens students’ memorization skills but also plays an important role in shaping noble character and spiritual awareness based on Qur’anic values. Therefore, integrating Tahfidz programs into educational institutions can serve as an effective strategy for developing students who are intellectually capable, spiritually mature, and morally grounded. Keywords: Spiritual Intelligence, Tahfidz Juz Amma, Qur’anic Learning, Character Development, Students.